2022
DOI: 10.3390/v14081631
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Autoimmune Diseases in Patients Hospitalized with COVID-19 in Spain: A Nation-Wide Registry Study

Abstract: We aimed to evaluate the clinical outcome of Systemic Autoimmune Diseases (SADs) patients hospitalized with COVID-19 in Spain, before the introduction of SARS-CoV-2 vaccines. A nationwide, retrospective and observational analysis of the patients admitted during 2020, based on the ICD10 codes in the National Registry of Hospital Discharges, was performed. Among 117,694 patients, only 892 (0.8%) presented any type of SAD before COVID-19-related admission: Sjogren’s Syndrome constituted 25%, Systemic Vasculitides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…If we covered mild patients in our study, there would be different results. The third case–control study conducted by Victor Moreno‐Torres et al 15 in 2022 found that the severity of pneumonia in RD patients was similar to that in the general population, which is similar to our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…If we covered mild patients in our study, there would be different results. The third case–control study conducted by Victor Moreno‐Torres et al 15 in 2022 found that the severity of pneumonia in RD patients was similar to that in the general population, which is similar to our results.…”
Section: Discussionsupporting
confidence: 91%
“…Abbreviations: CRP, C-reactive protein; D-D, D-dimer; ESR, erythrocyte sedimentation rate; IFNγ, interferonγ; IL-10, interleukin-10; IL-17, interleukin-17; IL-2, interleukin-2; IL-4, interleukin-4; IL-6, interleukin-6; IL-8, interleukin-8; LDH, lactate dehydrogenase; LY, lymphocyte; NE, neutrophil; RD, rheumatic diseases; SF, serum ferritin; TNFα, tumor necrosis factorα.verity of COVID-19 from aspects of gender, age and complications.If we covered mild patients in our study, there would be different results. The third case-control study conducted by Victor Moreno-Torres et al15 in 2022 found that the severity of pneumonia in RD patients was similar to that in the general population, which is similar to our results. which may relate to the fact that rheumatic immune diseases often invade connective tissue, and viral infection will further induce the aggravation of these symptoms.…”
supporting
confidence: 92%
“…A study in Spain concluded that the higher COVID-19 mortality rates seen in patients with systemic autoimmune diseases were related to the higher burden of comorbidities, secondary to direct organ damage and sequelae of their condition. 7 However, a study conducted on a cohort of SSc patients in Brazil reported that pulmonary arterial hypertension, interstitial lung disease, cardiac involvement, and use of rituximab, but not age, gender, comorbidities or use of corticosteroids, were predictors of worse outcome for COVID-19. 8 Therefore, apart from comorbidities, disease-related factors such as specific organ involvement and treatment history could also play a role in the outcome of SSc patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that COVID-19 is associated with a different degree of risk for various autoimmune diseases, including BD [15]. Also, Moreno-Torres and collaborators (2022) described the clinical outcome of systemic autoimmune disease patients hospitalized with COVID-19 in Spain [16]. The study included 117,694 patients and identified a higher mortality rate in systemic autoimmune disease patients that was related to the higher burden of comorbidities, secondary to direct organ damage and sequelae of their condition [16].…”
Section: Literature Reviewmentioning
confidence: 99%